2022
DOI: 10.3390/antiox11061099
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effects of Standardized Aronia melanocarpa Extract on Reproductive and Metabolic Disturbances in a Rat Model of Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) represents the most common endocrinopathy among childbearing-age women, with oxidative stress (OS) underlying its etiopathogenesis. Metformin (MET) represents a frequently used agent in PCOS. However, weak results encourage alternative treatments. We aimed to investigate isolated and synergistic effects of Standardized Aronia melanocarpa extract (SEA) and MET for alleviating reproductive and metabolic PCOS abnormalities. PCOS induction was followed by 28-day treatment with MET,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
3
5
0
Order By: Relevance
“…A similar trend was recorded in the clomiphene and metformin groups or in the combination of KH with both drugs. In agreement with previous studies [ 62 , 70 , 71 ], metformin and clomiphene were reported to reverse the elevated testosterone level in letrozole-induced PCOS rats. In women with PCOS, metformin causes a rapid decrease in LH-stimulated testosterone secretion [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…A similar trend was recorded in the clomiphene and metformin groups or in the combination of KH with both drugs. In agreement with previous studies [ 62 , 70 , 71 ], metformin and clomiphene were reported to reverse the elevated testosterone level in letrozole-induced PCOS rats. In women with PCOS, metformin causes a rapid decrease in LH-stimulated testosterone secretion [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, metformin treatment did not affect the antral follicles count in PCOS rats. Similar findings were observed in the past on the metformin effect on PCOS rat’s ovarian histology [ 65 ]. Interestingly, the combination of metformin with KH significantly increased the antral follicle and corpus luteum counts and reduced the cystic follicle count.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the combination of metformin with KH significantly increased the antral follicle and corpus luteum counts and reduced the cystic follicle count. Rudic et al revealed that the combination of Aronia melanocarpa with metformin reduced the cystic follicle count and increased the corpus luteum count in PCOS rats [ 65 ]. Meanwhile, the combination of KH with clomiphene recorded the highest restoration of corpus luteum and antral follicles compared to all other treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Uzunsoy / Uluslararası Tarım Araştırmalarında Yenilikçi Yaklaşımlar Dergisi / International Journal of Innovative Approaches in Agricultural Research, 2022, Vol. 6 (4) Kähkönen, Hopia & Heinonen, 2001;Wu, Gu, Prior & McKay, 2004;Osmiańzski & Wojdylo, 2005;Jakobek, Šeruga & Krivak, 2011;Kapci, 2013;Tolić et al, 2015;Szopa et al 2017;Dąbrowska et al, 2019;Denev, Číž, Kratchanova & Blazheva, 2019;Rudic et al, 2022Brӓunlich et al, 2013Denev et al, 2019;Daoutidou, Plessas, Alexopoulos & Mantzourani, 2021;Deng et al, 2021Ohgami et al, 2005Martin et al, 2014;Kang et al, 2017;Lee et al, 2018;Jang, Lee, Choi & Yim, 2020;Ali et al, 2021;Li et al, 2022Bhaswant, Shafie, Mathai, Mouatt & Brown, 2017Jeon et al, 2018;Jeong & Kim, 2019;Chen, Zhu & Meng, 2020;Mu et al, 2020Xie et al, 2017Kim et al, 2018;Jeong & Kim, 2019;Tasic et al, 2021Bell & Gochenaur, 2006Naruszewicz, Laniewska, Millo & Dłuzniewski, 2007;Olas et al, 2008;Ćujić et al, 2018;Istas et al, 2019Malik et al, 2003Lala et al, 2006;Kędzierska et al, 2013;Choi et al, 2018a;Thi & Hwang, 2018;…”
Section: Phenolic Content Of Aronia and Related Antioxidant Activitymentioning
confidence: 99%